Evaluation and Solution for SAP Implementation Using Technology Acceptance Model: A Case Study in an Indonesian Food Trading Company - Mayang Ayu Andila; Raymond Sunardi Oetama (G-Tech: Jurnal Teknologi Terapan, 2023)
Several companies have implemented an end-to-end SAP system, but are experiencing problems. To find the root cause of this problem, this study evaluates employee user acceptance of SAP in one company in Indonesia. The variables used are taken from the Technology Acceptance Model which includes Perceived Usefulness, Perceived Ease of Use, Attitude Toward Use, and also Behavioral Intention to Use. Furthermore, it was also found that the training did not affect Cooperation and the Perceived Ease of Use of the SAP System. The training was chosen as the root cause of the constraints on SAP implementation in this company. After the root cause of the problem is found, a solution is designed in the form of a website that aims to improve SAP training at this company.